A Note on How Prior Survey Experience With Self-Administered Panel Surveys Affects Attrition in Different Modes. (August 2020) - Gummer, Tobias; Daikeler, Jessica
Attrition poses an important challenge for panel surveys. With respect to these surveys, respondents' decisions about whether to participate in reinterviews are affected by their participation in prior waves of the panel. However, in self-administered mixed-mode panels, the way of experiencing a survey differs between the mail mode and the web mode. Consequently, this study investigated how respondents' prior experience with the characteristics of a survey—such as length, difficulty, interestingness, sensitivity, and the diversity of the questionnaire—affects their informed decision about whether to participate again or not. We found that the length of a questionnaire seems to be of such importance to respondents that they base their participation on this characteristic, regardless of the mode. Our findings also suggest that the difficulty and diversity of questionnaires are readily accessible information that respondents use in the mail mode when making a decision about whether to participate again, whereas these characteristics have no effect in the web mode. In addition, privacy concerns have an impact in the web mode but not in the mail mode.